Primary diaphragmatic undifferentiated pleomorphic sarcoma in a cat. Issue 1 (May 2021) - Bonazzi, Irene; Morabito, Simona; Brunetti, Barbara; Nicoli, Stefano; Valenti, Paola
Case summary: A 5-year-old neutered female domestic shorthair cat was referred for acute onset of dyspnoea. Thoracic radiographs performed by the referring veterinarian revealed the presence of pleural effusion. Upon presentation, the cat was dyspnoeic, and cardiopulmonary auscultation revealed muffled heart sounds and bilaterally increased bronchovesicular sounds. Radiographic study of the thorax revealed bilateral pleural effusion and a soft tissue opacity in the dorsocaudal region of the left hemithorax. A whole-body contrast-enhanced CT scan identified a soft tissue mass arising from the left diaphragmatic crus. Transthoracic ultrasound-guided fine-needle aspiration (FNA) of the mass was performed and the result was consistent with a malignant mesenchymal neoplasia, showing giant cells. Cytoreductive surgery was performed and the histopathology diagnosis of undifferentiated pleomorphic sarcoma was made. Adjuvant chemotherapy was then offered. Ten days after surgery pleural effusion recurred. Thoracic echography revealed the presence of a diaphragmatic thickening in the area of surgical resection. FNA of the thickening was consistent with mesenchymal neoplasia. Even when chemotherapy and supportive treatment with pain relief was instituted, the clinical condition of the cat worsened within a few days and it was euthanased 1 month after surgery. Relevance and novel information: Primary diaphragmatic tumours (PDTs) have been rarely reported in human and in veterinary medicine, where only three cases have been described in the dog. To our knowledge, this is the first report to describe a PDT, specifically an undifferentiated pleomorphic sarcoma, in a cat.